2013
DOI: 10.1097/hjh.0b013e32836157be
|View full text |Cite
|
Sign up to set email alerts
|

Blood pressure response with fixed-dose combination therapy

Abstract: Overall, the combination of olmesartan and HCTZ is as effective as olmesartan and CCB in lowering 24-h, daytime, and night-time ambulatory BP. However, greater lowering is noted with the olmesartan and CCB combination for clinic BP. Thus, out-of-office BP monitoring is necessary to provide better assessment of overall BP and response to treatment. Women and diabetic individuals may have slightly better 24-h ambulatory BP response with the olmesartan and CCB combination therapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…Women experienced better antihypertensive response overall, and specifically to thiazides, ARBs, and combinations. Agarwal et al [5] also showed that women had better antihypertensive response to combinations (both, CCBs plus olmesartan and thiazide diuretics plus olmesartan) than men.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Women experienced better antihypertensive response overall, and specifically to thiazides, ARBs, and combinations. Agarwal et al [5] also showed that women had better antihypertensive response to combinations (both, CCBs plus olmesartan and thiazide diuretics plus olmesartan) than men.…”
Section: Discussionmentioning
confidence: 99%
“…[1,19,23,24] A smaller response of these patients to beta-blockers and to ACEIs/ARBs, as well as a greater BP reduction with diuretics and CCBs, has been reported. [2,5,6] The meta-regression shows an overall response lower than the median in Afro-American patients treated with beta-blockers as compared to other ethnicities.…”
Section: Discussionmentioning
confidence: 99%
“…This was demonstrated by the ATOM study and its importance had already been invoked by other publications. [1317]…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing body of evidence which shows that antihypertensive therapy substantially reduces the incidence of cardiovascular disease, provided that the blood pressure (BP) is controlled tightly. 1 , 2 To achieve sufficiently tight BP control, it is often necessary to employ combination therapy with multiple antihypertensive agents of different classes, 3 , 4 , 5 , 6 , 7 , 8 but the optimum combination has not yet been elucidated. In recent clinical practice, an angiotensin receptor blocker (ARB) combined with a calcium channel blocker (CCB) or an ARB combined with a diuretic have been widely used for the treatment of hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…In recent clinical practice, an angiotensin receptor blocker (ARB) combined with a calcium channel blocker (CCB) or an ARB combined with a diuretic have been widely used for the treatment of hypertension. 6 However, it is still unclear which combination is more beneficial for the prevention of cardiovascular disease, as well as which is better with regard to safety and tolerability. Combination of olmesartan and a CCB or a diuretic in Japanese elderly hypertensive patients (COLM) trial was a prospective, randomized, open-label, blinded-endpoint (PROBE) study to determine which combination is a preferable therapy for hypertension, ARB plus CCB or ARB plus diuretic, 9 , 10 and the principal results have demonstrated that there were no remarkable differences in the primary composite endpoints of cardiovascular morbidity and mortality between the two groups, olmesartan plus CCB or diuretic.…”
Section: Introductionmentioning
confidence: 99%